Neonatal patients with melioidosis: a systematic review - Chantal Edwardes; Isaac Jarratt-Barnham (BMC Infectious Diseases)
Abstract Background Melioidosis is a neglected, but increasingly prevalent, tropical disease. Whilst rare in neonates, it has been associated with high mortality in this population. Despite this, little work focusing on neonatal melioidosis has been undertaken. Here, we report the first PRISMA-compliant systematic review exploring the clinical characteristics of culture- confirmed melioidosis in neonates. Method We searched several databases, including Web of Science, WHO Global Index, Scopus and Ovid, for primary studies reporting a case of neonatal melioidosis. Study quality was assessed using the Methodological Index for Non-Randomized Studies (MINORS) tool and the Oxford Levels of Evidence. 50 neonatal cases were identified across 24 publications. Of these, 26 cases from 19 papers were reported in sufficient detail to enable analysis. Results All studies identified were of poor quality, and largely consisted of case reports, with little uniformity in study reporting. However, the cases typically occurred in the early neonatal period, presented with symptoms atypical of melioidosis in other populations and showed a high mortality rate of over 65%. Importantly, instances of vertical transmission were identified, which is likely under-recognized and under-reported. Conclusions This review demonstrates substantial need for further work to build the evidence base surrounding this neglected pathology. Despite this, we identified a number of features of the disease in this population that may inform diagnosis and management. We also note several common barriers preventing effective treatment, including lack of a rapid diagnostic testing, lack of clinician awareness and high levels of antibiotic resistance.